Mental Workload and Job Satisfaction in Healthcare Workers: The Moderating Role of Job Control - Rostami, Fatemeh; Babaei-Pouya, Amin; Teimori-Boghsani, Gholamheidar; Jahangirimehr, Azam; Mehri, Zahra; Feiz-Arefi, Maryam (Frontiers in Public Health, 2021)
Objective: The aim of this study was to investigate the moderating role of job control in relation to mental workload and job satisfaction of healthcare workers. Methods: This cross-sectional study was carried out on 480 nurses, midwives, and administrative workers in four educational hospitals of Ardabil, Iran. Research tools were included demographic information questionnaire, NASA-TLX questionnaire, job description index (JDI) questionnaire and job control inquiry. Results: Compared with administrative workers, mental workload of nurses and midwives was significantly higher and likewise mental workload of nurses was significantly difference compared to midwives (P < 0.001). Nurses and midwives had substantially higher job satisfaction than administrative workers (P < 0.001). Also, nurses and midwives had higher job control than administrative workers (P < 0.001 and P = 0.002, respectively). Based on the designed model, the correlation between mental workload and job satisfaction was negative and significant (r = −0.22); which in the presence of job control, the relationship between the two variables of workload and job satisfaction slightly increased (r = −0.19, P < 0.001). These conditions were the same in the three job groups separately. Conclusion: Mental workload is inversely related to job satisfaction and job control. Job control plays an important role in improving working conditions in healthcare workers.